Health related quality of life outcomes following stereotactic body radiotherapy in patients with oligo-metastatic disease: A systematic review and individual patient data meta-analysis. (August 2022) - Barry, Aisling S.; Helou, Joelle; Bezjak, Andrea; Wong, Rebecca; Dawson, Laura A.; Ringash, Jolie; Fazelzad, Rouhi; Liu, Zhihui; Olson, Robert; Palma, David; Ost, Piet; Siva, Shankar; et al.
Highlights: Reported health-related quality of life (HRQOL) outcomes are lacking in patients with oligo-metastatic disease (OMD) Little is known of the impact of metastatic directed therapies, such as stereotactic body radiotherapy (SBRT), on short and long-term HRQOL. SBRT does not appear to adversely affect HRQOL over time in patients with OMD. More robust assessment and reporting of HRQOL in studies of OMD is needed. Abstract: Introduction: Published health-related quality of life (HRQOL) outcomes are lacking in patients treated for oligo-metastatic disease (OMD). The aim of this systematic review and individual patient data meta-analysis is to determine the effect of stereotactic body radiotherapy (SBRT) on HRQOL outcomes of patients with OMD. Methods: Studies screened included adults with extra-cranial OMD, defined as ≤ 5 metastases, SBRT intended as definitive treatment, and HRQOL as primary or secondary outcome. Primary outcome was change in HRQOL at 12-months from baseline in patients with OMD who received SBRT (versus not), reported as standardized mean difference (SMD). Results: A total of 7556 publications were identified, four studies met inclusion criteria (2 single arm interventional studies and 2 randomised controlled trials [RCTs]), and individual patient data was available from 3 studies (175 patients). In the two RCTs, there was no SS difference in the SMD between patients who received SBRT and those that did not (0.09 [95 % CI −0.32, 0.5], P = 0.66). On meta-analysis of patients (N = 107) who received SBRT the SMD was −0.23 (95 % CI [−0.42, −0.04], versus −0.25 (95 % CI [−0.57, 0.07]) in those who did not (N = 37) receive SBRT, demonstrating a small deterioration from baseline. Conclusion: In patients with OMD, there is no difference in HRQOL at 12-months from baseline between patients who received SBRT and those that did not. However, a small HRQOL deterioration was found in both groups of patients. More in-depth analysis of relevant HRQOL domains, in the setting of OMD, is required to better understand the potential impact of SBRT.